CARAȘ - SEVERIN COUNTY – A GREAT CANVAS FOR ENTREPRENEURIAL DEVELOPMENT IN THE FIELD OF TOURISM - Suzana Demyen; Venera Manciu (Annals of the University of Oradea: Economic Science, 2018)
The county of Caraş Severin, as well as the region of Mountainous Banat as a whole, presents a major development potential in all fields of activity, with many entrepreneurial perspectives. Much of this still remains untapped, although at least one field – the tourism area is particularly remarkable, and some of the tourist attractions, both natural and anthropic, are of great value, being recognized at national level. However, the managerial weaknesses as well as the very low level of investments made in recent years have contributed to the stagnation or even regression in terms of development from this point of view. From a geographic point of view, Caraş Severin County is on the third place as an area in the hierarchy of counties, the relief forms being numerous and various, both plains, reservoirs, as well as balneoclimatic and mountain resorts, the Danube Gorge. Anthropic objectives join the natural ones, with a number of Geto-Dacian or medieval vestiges, churches, monasteries, museums. However, the situation of tourism at the county level is not exceptional, with a number of deficiencies of several types. In order to analyze this, it is necessary first to observe the situation at national level.A closer analysis regarding the Romanian business environment indicates a general deterioration, partly due to the effects of the fiscal environment (as presented by the EY Barometer, 2013). And in terms of the number of enterprises and the period of their presence on the market, we can see that both the urban environment and the rural environment need to be given a much more serious level of attention, taking into account the fact that the process of transition to the market economy has generated mostly at rural level, multiple economic and social problems in almost all areas of activity. There is a need for actions in the process of identification of solutions in order to solve the problems of the Romanian business environment and the training of specialists in areas where there are gaps in development. We will continue to focus on the tourism and entrepreneurial potential in the area of Caraş Severin County, but we are initially looking at a brief overview of the analysis of the general business potential in rural areas in the region, as presented through statistical data (INSSE, 2016) reffering to the tourism in Caras Severin.